Book review: Volcanology. Processes, Deposits, Geology and Resources, by Ray Cas, Guido Giordano, John V. Wright, 2024. Springer Textbooks in Earth Sciences, Geography and Environment (STEGE); 1833 pages. Hardcover: price € 160.49, eBook: price € 117.69, ISBN: 978-3-319-66612-9 - Scarpati, Claudio (Geologos, 2024)
Book review: Volcanology. Processes, Deposits, Geology and Resources, by Ray Cas, Guido Giordano, John V. Wright, 2024. Springer Textbooks in Earth Sciences, Geography and Environment (STEGE); 1833 pages. Hardcover: price € 160.49, eBook: price € 117.69, ISBN: 978-3-319-66612-9